Dinosaur Bob and his adventures with the family Lazardo - Joyce, William ([New York] : Harper & Row, 1988)
While vacationing in Africa, the Lazardo family finds and brings back to America a friendly dinosaur that becomes the talk of the town.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Booklist Editors' (Reviewers') Choice
3.8
K-3
Keywords: Dinosaurs -- Fiction; Dinosaurs -- Fiction; Family life -- Fiction